Evaluation of the Globally Harmonized System Implementation in the Occupational Safety Division of the Manpower and Transmigration Department Surabaya - Afrian Eskartya Harjono; Tri Martiana; Shintia Yunita Arini; Mohd Rafee Baharudin; Erianto Fanani (Universitas Airlangga, 2022)
Introduction: The number of chemicals is increasing every year. Laboratories record work accidents because there are several chemicals that are not labeled and unidentified but are stored in an inappropriate place. The Globally Harmonized System (GHS) is a Global System for standardizing criteria and harmonizing hazard classification systems, Safety Data Sheets (SDSs) and Labeling. This research aims to assess and evaluate the implementation of the GHS at the Occupational Safety Division of the Manpower and Transmigration Department Surabaya. Methods: This research was a descriptive observational study. Data were collected by assessing 80 types of chemicals through assessment sheets and an interview with the analyst supervisor, who had responsibility and authority in the application of the GHS. This research aims to apply the GHS with hazard classification variables, SDS availability and suitability, and labelling availability and suitability. Results: The results showed that the implementation of the GHS at the Occupational Safety Division of the Manpower and Transmigration Department Surabaya was 66.67%, categorized as good, with a good availability and suitability assessment of SDSs of 91%, and a good availability and appropriateness assessment of labelling of 98.1%. Conclusion: The results showed that the Occupational Safety Division of the Manpower and Transmigration Department Surabaya has been very good at implementing the GHS, but some points must be made to maintain and improve the application of the GHS as an effort to prevent accidents with hazard communication.